A THEORETICAL VISION OF THE STRATEGY OF DEVELOPING THE PRIVATE SECTOR IN HUMAN DEVELOPMENT IN ARAB SOCIETIES - Prof. Ishaq Yousef Al-Ayyash (American Journals, 2023)
This research aims to develop a theoretical vision for the strategy of developing the private sector in human development in Arab societies, and the researcher adopted the descriptive approach in analyzing the research problem. The research has three axes, the first axis dealt with the development of the private sector between (difficulties and obstacles), the second axis included the role of the private sector in developing human resources, while the strategy for developing the private sector in our societies came in the third axis.The research reached a set of conclusions and recommendations, and among the conclusions is the need to provide an appropriate and stimulating climate that helps to carry out investment activity, through a number of procedures that reflect the best economic, legal and political conditions for private sector activity. In increasing their commercial activity due to the national and expatriate workforce, and developing solutions to address these problems in order to achieve development and prosperity, which will reflect positively on development.